Effectiveness of self-control and cyberloafing on employee performance - Levana Bening Hafizh; Yelli Eka Sumadhinata (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to examine and analyze the effect of self-control and cyberloafing on employee performance. This study uses primary data by taking the population used in the study to select CV companies. Galiya Corp. which is located in Bekasi City uses 40 respondents who work in the company. The method used is a type of quantitative research with survey methods. Data collection techniques by using questionnaires to respondents' employees' CV. Galiya Corp lives or offline. The data processing method in this study uses SPSS 25 software which is used in testing the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, t-test, and f test. The results obtained from this study are that H1 is accepted that the self-control and cyberloafing variables simultaneously affect the employee performance variable as seen from the f test, the Sig value is 0.000 <0.05. The self-control variable is the most dominant in influencing employee performance in CV. Galiya Corp can be seen in the results of multiple regression analysis with a coefficient of 0.721.